A Crack Propagation Control Study of Directional Hydraulic Fracturing Based on Hydraulic Slotting and a Nonuniform Pore Pressure Field - Yugang Cheng; Zhaohui Lu; Xidong Du; Xuefu Zhang; Mengru Zeng (Geofluids)
Hydraulic fracturing techniques for developing deeply buried coal reservoirs face routine problems related to high initial pressures and limited control over the fracture propagation direction. A novel method of directional hydraulic fracturing (DHF) based on hydraulic slotting in a nonuniform pore pressure field is proposed. A mechanical model is used to address crack initiation and propagation in a nonuniform pore pressure field, where cracks tend to rupture and propagate towards zones of high pore pressure for reducing the effective rock stress more. The crack initiation pressure and propagation morphology are analyzed by rock failure process analysis software. The numerical results show that the directional propagation of hydraulic fracturing cracks is possible when the horizontal stress difference coefficient is less than or equal to 0.5 or the slotting deviation angle is less than or equal to 30°. These findings are in good agreement with experimental results, which support the accuracy and reliability of the proposed method and theory.